Transcutaneous electrical acupoint stimulation for pregnancy outcomes in women undergoing in vitro fertilization-embryo transfer: A systematic review and meta-analysis - Yang, Han; Hu, Wen-hui; Xu, Gui-xing; Yin, Zi-han; Yu, Si-yi; Liu, Jia-jia; Xiao, Zhi-yong; Zheng, Xiao-yan; Yang, Jie; Liang, Fan-rong (Frontiers in Public Health, 2022)
Background Infertility is a common health problem affecting couples of childbearing age. The proposal of in vitro fertilization-embryo transfer (IVF-ET) solves the problem of infertility to a certain extent. However, the average success rate of IVF-ET is still low. Some studies conclude that transcutaneous electrical acupoint stimulation (TEAS) could improve pregnancy outcomes in women undergoing IVF-ET, however, there is a lack of comprehensive synthesis and evaluation of existing evidence. Objective To conduct a systematic review and meta-analysis to assess whether TEAS is effective and safe to improve the pregnancy outcomes for women undergoing IVF-ET. Methods Eight online databases were searched from inception to 19 November 2021. In addition, four clinical trial registries were also searched, relevant references were screened, and experts were consulted for possible eligible studies. Randomized controlled trials (RCTs) that included patients with infertility who underwent IVF and used TEAS as the main adjuvant treatment vs. non-TEAS or mock intervention controls were included. The clinical pregnancy rate (CPR) was considered the primary outcome. High-quality embryo rate (HQER), live birth rate (LBR), biochemical pregnancy rate (BPR), ongoing pregnancy rate (OPR), early miscarriage rate (EMR), birth defects rate (BDR), and adverse events related to interventions were regarded as secondary outcomes. The selection, data extraction, risk of bias assessment, and data synthesis were conducted by two independent researchers using Endnote software V.9.1 and Stata 16.0 software. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) system was used to evaluate the evidence quality of each outcome. Results There were 19 RCTs involving 5,330 participants included. The results of meta-analyses showed that TEAS can improve CPR [RR = 1.42, 95% CI (1.31, 1.54)], HQER [RR = 1.09, 95% CI (1.05, 1.14)], and BPR [RR = 1.45, 95% CI (1.22, 1.71)] of women underwent IVF-ET with low quality of evidence, and improve LBR [RR = 1.42, 95% CI (1.19, 1.69)] with moderate quality of evidence. There was no significant difference in EMR [RR = 1.08, 95% CI (0.80, 1.45)] and BDR [RR = 0.93, 95% CI (0.13, 6.54)] with very low and moderate quality of evidence, respectively. A cumulative meta-analysis showed that the effective value of TEAS vs. controls was relatively stable in 2018 [RR = 1.52, 95% CI (1.35, 1.71)]. In addition, no serious adverse events associated with TEAS were reported. Conclusion Our findings suggest that TEAS may be an effective and safe adjuvant treatment for women undergoing IVF-ET to improve pregnancy outcomes. However, the current evidence quality is considered to be limited, and more high-quality RCTs are needed for further verification in the future. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42021238871, identifier: CRD42021238871.